ANALISIS KOMPOS AMPAS TEBU DENGAN PERBEDAAN PENGECILAN UKURAN BAHAN BAKU DAN JENIS BIOAKTIVATOR - Sari, Cut Mulia; Rahmiati, Tengku Mia; Karnilawati, Karnilawati (Jurnal Sains Riset, 2022)
Sugarcane Bagasse is one of the wastes come out from the sugarcane water milling which is currently very much and very abundant in Pidie. Since this garbage cannot naturally disintegrate, it might harm the environment. One way to manage the sugarcane bagasse is by processing become compost. This study examined the results of sugarcane bagasse composting by using a reduction treatment in material size and the addition of several types of bioactivators that aim to accelerate the composting process and obtain the results that fulfil the requirements qualified. This study compraised of two factors, namely the reduction of size material factor and the type of bioactivator factor by using the Completely Randomized Design method. The results showed that the lowest value of C-Organic was obtained in the milling treatment and Orgadec bioactivator, N-total was obtained from manual counting treatment and MA11 bioactivator, the best C/N ratio was obtained in the milling treatment and Orgadec bioactivator, also the highest organic matter value was obtained in manual counting and EM4 bioactivator. Keywords : Compost, Sugarcane Bagasse, EM4, MA11, Orgadec